Tipping the scales: how fire controls the balance among functional groups in Angolan grasslands. Issue 1 (2nd January 2022) - Meller, Paulina; Frazão, Raquel; Lages, Fernanda; Jürgens, Norbert; Finckh, Manfred
Abstract : Fire plays an important role in the ecology of tropical grasslands globally. However, detailed studies comparing the response of plant functional groups to fire seasonality, and thus phenological timing, are scarce from humid Afrotropical grasslands. Such information, however, is crucial for understanding what keeps the grasslands open and for enabling evidence-based management, and conservation. We initiated an experiment in frost- and fire-prone Angolan geoxyle grasslands in 2017, investigating the effect of different timing of fires on cover and diversity of trees, grasses, geoxyles and herbs. We installed permanent, randomised plots with fire exclusion, annual early and late dry-season burning, representing the local burning practices. Functional plant groups reacted differently to the treatments, becoming apparent at species level and their performance metrics. After three years, grass species benefitted from late and no burning, and herbs from late burning, whereas geoxyles thrived under early burning. Tree growth was suppressed under late burning, and did not increase with fire exclusion. Species richness and diversity was higher in burnt than in unburnt plots. Seasonal timing of fire tips the scales between geoxyles and grasses. The extraordinary plant diversity of Angolan geoxyle grasslands is a result of pyrodiversity and frost, keeping the grasslands open even in absence of fire.